Ag-GaP Schottky photodiodes for UV sensors. - Pikhtin, A.N (IEEE Transactions on electron devices)
We created UV-sensitive photodiodes based on a GaP Schottky barrier. A revised value of the Ag-GaP barrier height (1.55±0.03 eV) has been determined, and this value is much larger than commonly used for this system. Moreover, it depends on the parameters of the dielectric spacer and may be up to 1.7 eV. The high Schottky barrier improves the characteristics of photodetectors. We developed two types of such photodetectors. The first one is a selective UV photodiode with λmax=0.32 μm, Δλ=15 nm, and S=0.034 A/W based on the selective transparency of silver. The second one is a broad-band with λmax=0.42 μm, Δλ=230 nm, and S=0.19 A/W.